MOTIVASI PEMELIHARAAN KESEHATAN GIGI DAN MULUT (PERIODONTITIS) PASIEN DIABETES MELITUS MENGGUNAKAN MEDIA LEAFLET (Studi di Puskesmas Maron Kabupaten Probolinggo) - Jihan Kusdiana Fadila; Ida Chairanna Mahirawatie; Soesilaningtyas Soesilaningtyas (Politeknik Kementerian Kesehatan Banjarmasin, 2021)
One of the complications of diabetes mellitus in the field of dentistry is oral diabetic including dry mouth (xerostomia), bleeding gums (gingivitis), tartar (calculus), alveolar bone resorption, and periodontitis. Periodontitis is a complication that often occurs in people with diabetes mellitus with high prevalence rates up to 75% (Nandya, et al, 2012 in Lestari, et al, 2016). The City of Probolinggo itself has a proportion of dental and oral health problems of approximately 65% ​​- 70% and those caring for teeth approximately 8.5% - 10% of the population of 217,062 people. The problem with this research is the high prevalence of periodontitis in the Maron Public Health Center, Probolinggo Regency. This study aims to find out Motivation about the Maintenance of Dental and Oral Health (Periodontitis) in Diabetes Mellitus Patients in Maron Health Center, Probolinggo Regency. The method is by filling questionnaires and examinations, this type of research is descriptive targeting 30 people with Diabetes Mellitus. The results showed that motivation for encouragement included strong (75%), motivation for strong expectations (71%), motivation for strong reward (59%). It can be concluded that the motivation of Diabetes Mellitus patients about oral health is strong (69%). Keyword : motivation, health maintenance, diabetes mellitus, leaflets.